Comparison of Efficacy of Bolus Dosages of Norepinephrine, Phenylephrine, and Ephedrine in Treating Post-Spinal Hypotension During Elective Cesarean Section: A Randomized Double-Blinded Controlled Trial - Ganeshnavar, Anilkumar Sangappa; Endigeri, Archana; Chitti, Prashant Kumar Reddy; Nair, Vinduja; Konappanavar, Chaitra (Faculty of Medicine, Brawijaya University, 2024)
Background: Phenylephrine and ephedrine are widely used to manage spinal-induced hypotension after cesarean section. Norepinephrine is an alternative vasopressor that maintains the heart rate. This study compared the efficacy and safety of bolus administration of norepinephrine, phenylephrine, and ephedrine for treating post-spinal hypotension during elective cesarean section.Methods: This prospective, randomized, double-blind controlled trial included patients between 20–45 years of age undergoing elective cesarean section; they were randomized into three groups receive norepinephrine 6 µg (Group A, n = 45), phenylephrine 100 µg (Group B, n = 45), or ephedrine 6 mg (Group C, n = 45) boluses after a 20% drop in blood pressure. The primary objective was to compare the efficacy (total doses required) and safety (maternal complications) of treating post-spinal hypotension. Secondary objectives assessed neonatal outcomes using fetal arterial blood gas and Apgar scores. Mean differences were analyzed using one-way analysis of variance at a 95% confidence level (α = 0.05).Result: The total number of drug boluses required to treat maternal hypotension was significantly lower in group A (1.78 ± 0.74) than in groups B (1.93 ± 0.69) and C (2.38 ± 0.81) (F = 7.89; p < 0.001). Tachycardia occurred more frequently in group C (37.8%) than in groups A (15.6%) and B (26.7%) (p = 0.001). The incidence of bradycardia was higher in group B (24.4%) than in groups A (20%) and C (6.7%) (p = 0.001). Maternal complications were comparable between the groups, with no significant differences in neonatal outcomes.Conclusion: Norepinephrine is a potent drug with a better hemodynamic profile than phenylephrine and ephedrine.